Nationalism—a way to resistance: A case study of Darwish’s poetry - Alkahlan, Hessa (International Journal of Language and Literary Studies, 2023)
This study addresses the way Palestinian literature asserts Palestinian national identity. Practitioners of Palestinian poetry have dedicated it as a response to the Zionist claim that “Palestine is a ‘land without a people for a people without a land.’” In the context of the Palestinian–Israeli struggle, and the accompanying discourses by Israeli occupiers to deprive the Palestinians of the right to live on their own land, the Palestinians followed different paths to defend their rights and pursue their cause; while some chose military resistance, others chose cultural resistance. Considering this, this study will examine Mahmoud Darwish’s attempt to achieve the “autonomy, equality and recognition” of the Palestinians through his selected poems. Taking Darwish (1941-2008) as an example, it will focus on how poetry is utilized to defend the Palestinian nation by re-establishing Palestinians’ real image as a people at present and connecting it to Palestine as a historical homeland.